Chloroquine-primaquine versus chloroquine alone to treat Vivax malaria in Afghanistan: An open randomized superiority trial. - Awab, G; Imwong, M; Bancone, G; Jeeyapant, A; Day, N; White, N; Woodrow, C (American Journal of Tropical Medicine and Hygiene, 2017)
Background Afghanistan’s national guidelines recommend primaquine for radical treatment of P. vivax malaria but this is rarely implemented because of concerns over potential hemolysis in patients who have G6PD deficiency. Methods Between August 2009 and February 2014, we conducted an open-label, randomized controlled trial of chloroquine (CQ) alone versus chloroquine plus primaquine (0.25mg base/kg/day for 14 days)(CQ+PQ) in patients aged > 6 months with microscopy confirmed P. vivax infection. In the CQ+PQ group G6PD deficiency was excluded by fluorescent spot testing. The primary outcome was P. vivax recurrence assessed by survival analysis. Results Of 593 patients enrolled, 570 attended at or after 14 days of follow-up. P. vivax recurrences occurred in 37 (13.1%) of 282 patients in the CQ+PQ arm versus 86 (29.9%) of 288 in the CQ arm . Cox Proportional Hazard Ratio 0.37, 95% CI 0.25 – 0.54) (ITT analysis). Protection against recurrence was greater in the first six months of follow-up (HR 0.082; 95% CI 0.029-0.23) than later (HR 0.65, 95% CI 0.41-1.03). Five of seven patients requiring hospital admission were considered possible cases of PQ-related hemolysis, and PQ was stopped in a further six; however in none of these cases did hemoglobin fall by >2g/dl or to below 7 g/dl. Conclusions Primaquine 0.25mg/kg/day for 14 days prevents relapse of P. vivax in Afghanistan. Patient visits during the first week may improve adherence. Implementation will require deployment of point of care phenotypic tests for G6PD deficiency.